Perspectives on Immunotherapy of Metastatic Colorectal Cancer - Dai, Yongjiu; Zhao, Wenhu; Yue, Lei; Dai, Xinzheng; Rong, Dawei; Wu, Fan; Gu, Jian; Qian, Xiaofeng (Frontiers in Oncology, 2021)
Colorectal cancer, especially liver metastasis, is still a challenge worldwide. Traditional treatment such as surgery, chemotherapy and radiotherapy have been difficult to be further advanced. We need to develop new treatment methods to further improve the poor prognosis of these patients. The emergence of immunotherapy has brought light to mCRC patients, especially those with dMMR. Based on several large trials, some drugs (pembrolizumab, nivolumab) have been approved by US Food and Drug Administration to treat the patients diagnosed with dMMR tumors. However, immunotherapy has reached a bottleneck for other MSS tumors, with low response rate and poor PFS and OS. Therefore, more clinical trials are underway toward mCRC patients, especially those with MSS. This review is intended to summarize the existing clinical trials to illustrate the development of immunotherapy in mCRC patients, and to provide a new thinking for the direction and experimental design of immunotherapy in the future.